The G308A Polymorphism of the Tumor Necrosis Factor-alpha Gene and the Inflammatory Mechanism of Chronic Venous Insufficiency of the Lower Extremities (Eurasian Scientific Herald, 2026)
Oxidative stress is a core mechanism of secondary injury after traumatic brain injury (TBI). Mitochondrial manganese superoxide dismutase, encoded by SOD2, is the principal defence against the superoxide radical, and the common Ala16Val polymorphism (rs4880) alters import of the enzyme into mitochondria and its protective capacity. We aimed to determine the distribution of SOD2 rs4880 in patients with TBI, to relate it to serum malondialdehyde (MDA) as a marker of lipid peroxidation, and to assess its association with oxidative-stress-related secondary complications and 6-month functional outcome. The rare APOE variant rs769452 was examined as an exploratory secondary analysis only.